2012
DOI: 10.3109/08941939.2011.639849
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Nigella Sativa Oil on Intestinal Damage in Necrotizing Enterocolitis

Abstract: NSO significantly reduced the severity of intestinal damage in NEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…There are few experimental studies that evaluated the effects of NS oil or NS main active component known as thymoquinone in animal models of disease. The results of these studies have shown that NS oil and thymoquinone increased the activity of antioxidant enzymes and weight gaining as well as decreased inflammatory and oxidative stress factors, and tissue damage in experimental models of colitis (Emekli‐Alturfan et al, ; Isik et al, ; Lei et al, ; Tayman et al, ). These discrepancies might be due to usage of active components of NS in experimental studies, which are more effective than pure NS powder.…”
Section: Discussionmentioning
confidence: 99%
“…There are few experimental studies that evaluated the effects of NS oil or NS main active component known as thymoquinone in animal models of disease. The results of these studies have shown that NS oil and thymoquinone increased the activity of antioxidant enzymes and weight gaining as well as decreased inflammatory and oxidative stress factors, and tissue damage in experimental models of colitis (Emekli‐Alturfan et al, ; Isik et al, ; Lei et al, ; Tayman et al, ). These discrepancies might be due to usage of active components of NS in experimental studies, which are more effective than pure NS powder.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid peroxidation level was measured with the thiobarbituric acid reaction according to the method of Ohkawa et al [14]. Superoxide dismutase (SOD) activities were determined according to the method of Sun and Oberley [15,16]. The principle of the method is based on the inhibition of nitroblue tetrazolium reduction by the xanthine-XO system as a superoxide generator.…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Tissue GSH-Px and SOD levels were significantly preserved in the NEC + NSO group (P<0.05), whereas, tissue MDA, MPO levels of the NEC+NSO group were significantly lower than those in the NEC group (P<0.05). It is concluded that NSO significantly reduced the severity of intestinal damage in NEC [84] . A study was designed to determine whether treatment with TQ prevents and ameliorates colonic inflammation in a mouse model of inflammatory bowel disease.…”
Section: Gastro-protective Activitymentioning
confidence: 99%